2015
DOI: 10.1111/vop.12285
|View full text |Cite
|
Sign up to set email alerts
|

Protozoal infections of the cornea and conjunctiva in dogs associated with chronic ocular surface disease and topical immunosuppression

Abstract: Protozoal keratitis and conjunctivitis without systemic involvement appears rare and may be associated with chronic preexisting ocular surface disease treated with long-term immunosuppression. Based upon clinical appearance, lesions could be confused with neoplasia. This is the first report of amoebic keratoconjunctivitis in dogs and of L. mexicana in dogs in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…The role of cyclosporine in the development of ICK requires further investigation; however, it is plausible that this medication contributed to the local immunosuppressed state that permitted development of ICK in the dogs of this report. Atypical corneal infections are previously described in dogs during cyclosporine therapy . Some of the dogs described in this series were also affected by immunosuppressive systemic diseases or receiving immunosuppressive systemic therapeutics.…”
Section: Discussionmentioning
confidence: 76%
“…The role of cyclosporine in the development of ICK requires further investigation; however, it is plausible that this medication contributed to the local immunosuppressed state that permitted development of ICK in the dogs of this report. Atypical corneal infections are previously described in dogs during cyclosporine therapy . Some of the dogs described in this series were also affected by immunosuppressive systemic diseases or receiving immunosuppressive systemic therapeutics.…”
Section: Discussionmentioning
confidence: 76%
“…A reduction of IFN‐γ may also reduce the anti‐parasitic ability of macrophages, natural killer cells and nonimmune cells, hence allowing intracellular growth, transmission and proliferation of T gondii . Systemic toxoplasmosis has been described after monotherapy with ciclosporin in cats and localized toxoplasmosis may also occur in cats and dogs . However, it must be noted that fatal toxoplasmosis in cyclosporine‐treated cats is uncommon and a direct inhibitory effect of ciclosporin metabolites on T gondii proliferation has also been described .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reported cases of pyogranulomatous keratitis in the dog identified several protozoal organisms (ex. Toxoplasma gondii and Leishmania ) as well as Acanthamoeba as causative agents with visualization of organisms followed by confirmatory ancillary testing [68]. The Beckwith-Cohen et al protozoal keratitis cases were all identified in dogs that had received long term, topical or systemic, immunosuppressive therapy for keratoconjunctivitis sicca before masses were noted to be progressing over the corneas.…”
Section: Discussionmentioning
confidence: 99%